Nanoparticles for tumor targeted therapy and preparation method thereof
By designing ZIF-8-GOx@Cu-PDA@liposome-LA nanoparticles, using the Cu-PDA shell to respond to GSH and activate GOx under ultrasound conditions, the targeting and low delivery efficiency in tumor-targeted therapy are solved. Problem, tumor-specific multimodal therapy has been achieved, significantly improving the therapeutic effect and reducing damage to normal cells.
Patent Information
- Application Number
- CN202411134744.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-19
AI Technical Summary
Existing tumor-targeted treatments are prone to off-targeting, poor therapeutic effects and inefficient delivery, especially the premature degradation of glucose oxidase in normal cells and tissues, resulting in therapeutic ineffectiveness and systemic toxicity.
A ZIF-8-GOx@Cu-PDA@liposome-LA nanoparticles were designed, and the ZIF-8-GOx core was prepared by co-precipitation method, and the surface was coated with copper dopamine (Cu-PDA) shell and lipids. Liposome-LA layer, Cu-PDA shell is GSH-responsively cleaved at the tumor site to avoid early degradation of GOx, ZIF-8 core activation catalyzes the generation of H2O2, and ROS and NO under ultrasound conditions, achieving tumor-specific multimodal state therapy.
Tumor-specific and efficient anti-tumor performance was achieved. In vitro and in vivo studies have shown that the system has accurate and efficient anti-tumor effects and has reduced toxicity to normal cells.
Smart Images

Figure CN119112832A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biological nanomaterials, and in particular relates to nanoparticles used for tumor targeted therapy and a preparation method thereof. Background Art
[0002] Cancer, characterized by abnormal cell metabolism and growth of cancer cells, remains a major threat to global human health. The special metabolic pattern of cancer cells (i.e., aerobic glycolysis) makes them more demanding on nutrients, especially glucose, and causes the accumulation of lactic acid in the tumor microenvironment. In recent years, starvation therapy, which "starves" tumor cells by blocking or consuming the supply of nutrients such as oxygen, glucose, lactic acid, and amino acids in the tumor, has become a major research hotspot. Based on the key role of glucose in tumor growth and proliferation and the sensitivity of cancer cells to changes in glucose concentration, glucose oxidase (GOx) has been widely studied in the design of starvation therapy systems by catalyzing the reaction of intracellular glucose and oxygen (O2) to produce hydrogen peroxide (H2O2) and gluconic acid to cut off the nutrient supply of cancer cells and aggravate intracellular hypoxia, acidification, and oxidative stress levels. However, the demand of normal cells for glucose supply and metabolism and the degradation characteristics of GOx by proteases often make GOx "off-target" and ineffective in starvation therapy during treatment, and cause inevitable systemic toxicity, which limits the further application of GOx in biomedicine.
[0003] In the process of realizing the present invention, the inventors found that there are at least the following problems in the prior art: targeted therapy is prone to off-target effects, poor therapeutic effects, and low delivery efficiency. Summary of the invention
[0004] The purpose of the present invention is to provide an ultrasound / GSH dual-responsive ZIF-8-GOx@CuPDA@liposome-LA nanoparticle and a preparation method and application thereof in view of the deficiencies in the prior art, so as to solve the problems existing in the related art such as easy off-target of targeted therapy, poor therapeutic effect and low delivery efficiency.
[0005] One of the technical solutions of the present invention is to provide a ZIF-8-GOx@Cu-PDA@liposome-LA nanomaterial, which has a three-layer structure: a ZIF-8-GOx core, a Cu-PDA layer and a liposome-LA layer, wherein the ZIF-8-GOx core is ZIF-8 encapsulated with glucose oxidase; in the Cu-PDA layer, copper ions are evenly distributed in polydopamine; in the liposome-LA layer, L-arginine is dispersed in liposomes. The Cu-PDA shell can specifically respond to GSH in the tumor site and cleave, which can avoid GOx from "off-targeting" in normal cells and tissues in advance. After the internal ZIF-8-GOx is exposed at the tumor site, Zn overload is triggered and GOx is activated to catalyze the reaction of intracellular glucose and oxygen to generate H2O2. The consumption of glucose can achieve starvation therapy, and work together with Zn ion therapy to aggravate cellular oxidative stress. H2O2 can also produce more active ROS under ultrasound catalysis. In addition, it can quickly react with L-arginine (LA) delivered by the liposome layer to produce high-concentration NO to achieve ultrasound-catalyzed gas therapy.
[0006] The second technical solution of the present invention is to provide a method for preparing a ZIF-8-GOx@Cu-PDA@liposome-LA (ZGCLL) nanomaterial, which prepares ZIF-8-GOx by using a coprecipitation method, and uses it as a template to coat a Cu-PDA shell on the surface, and on this basis, liposomes and LA are loaded on the surface of ZIF-8-GOx@Cu-PDA (ZGCP). The nanoparticles prepared in this embodiment are spherical and have a particle size of 100-300nm. Specifically, the present invention adopts the following steps:
[0007] Step 1. Add 10-12 mL of 0.194 g / mL 2-methylimidazole aqueous solution to 4-5 mL of 10 mg / mL GOx solution and stir at room temperature for 20 min, then add 4 mL of 25 mg / mL Zn(NO3)2·6H2O aqueous solution to the above solution; after stirring at room temperature for 30 min, add 20 mg of polyether F127 to the reaction system and continue the reaction for 2 h; the reaction product is centrifuged and washed with water for 3-4 times to obtain ZIF-8-GOx nanoparticles.
[0008] Step 2. Add 1-2 mL of 10 mg / mL ZIF-8-GOx nanoparticle dispersion and 100-200 μL of ammonia water to 10-16 mL of a mixed aqueous solution containing 8.75-12.5 mg of dopamine hydrochloride and 2-2.8 g of CuCl2·2H2O, and react for 5 hours in the dark; after the reaction, the product is centrifuged and washed with water 3-4 times to obtain ZGCP.
[0009] Step 3. DPPC, cholesterol and DSPE-mPEG are mixed in proportion to form a uniform solution; the uniform solution is added to chloroform and ultrasonically treated with an ultrasonic cleaner, and then evaporated to dryness using a rotary evaporator; the liposome sample is dissolved in water to prepare a liposome solution.
[0010] The mixing mass ratio of DPPC, cholesterol and DSPE-mPEG in the homogeneous solution is 6:4:0.5;
[0011] The ultrasonic treatment time is 10 min;
[0012] Step 4. Mix 1-1.25 mL of 10 mg / mL ZGCP dispersion with 80-100 μL of 0.45 mg / μL liposome solution and 1-1.25 g L-arginine, and perform ultrasonic treatment; centrifuge and wash with water for 3-4 times to obtain the target product ZGCLL, and the final product is spherical particles of 100-300 nm.
[0013] The third technical solution of the present invention is to provide an application of nanoparticles for tumor targeted therapy as ultrasound-assisted tumor therapeutic drugs, which is particularly effective under ultrasound synergy. The internal ZIF-8-GOx mediates Zn overload and activates GOx to catalyze the reaction of intracellular glucose and oxygen to generate H2O2. The consumption of glucose can achieve starvation therapy, and work together with Zn ion therapy to aggravate cellular oxidative stress. H2O2 produces more active ROS under ultrasound catalysis, and can also quickly react with the delivered LA to produce high-concentration NO to achieve ultrasound catalytic gas therapy.
[0014] Beneficial effects of the present invention: In vitro and in vivo studies have shown that this tumor-specific intelligent multimodal treatment system has precise and efficient anti-tumor performance.
[0015] The present invention can quickly respond to GSH and realize the rapid release of copper ions, and can release 16% of copper ions within 4 hours. The concentration of H2O2 in the solution after the present invention reacts with glucose for 12 hours and 24 hours is 429μM and 1069μM respectively. The present invention can produce 2.14μM NO within 24 hours, and can produce 9.43μM NO under ultrasonic conditions.
[0016] After the invention is mixed and cultured with mouse breast cancer cells 4T1 and human umbilical vein endothelial cells HUVEC, the survival rate of mouse breast cancer cells 4T1 is 2.6%, while the survival rate of human umbilical vein endothelial cells HUVEC is greater than 85%. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0018] Figure 1 Schematic diagram of the synthesis process of ZIF-8-GOx@Cu-PDA@liposome-LA and the ultrasound / GSH dual-response ion interference / starvation / gas synergistic treatment mechanism in the present invention
[0019] Figure 2 TEM images of ZIF-8-GOx at different magnifications in Example 1;
[0020] Figure 3 TEM images of ZGCP at different magnifications in Example 1;
[0021] Figure 4 is the energy dispersive X-ray spectrum (Cu, N, Zn and O) of ZGCP in Example 1 (scale: 200 nm);
[0022] Figure 5 XRD patterns of ZIF-8-GOx and ZGCP in Example 1;
[0023] Figure 6 (a) XPS full spectrum, (b) Zn 2p XPS spectrum and (c) Cu 2p XPS spectrum of ZGCP in Example 1;
[0024] Figure 7 It is the TEM image of ZIF-8 in Example 1;
[0025] Figure 8 TEM images of ZIF-8@Cu-PDA at different magnifications in Example 1;
[0026] Fig. 9 is the GSH standard curve;
[0027] Fig.10 is the GSH content in ZGCP (1 mg / mL) in Example 1 after reacting with different concentrations of GSH for 1 h;
[0028] Fig.11 (a) UV-Vis curves and (b) GSH quantitative results of the solution after the reaction of GSH (5 mM) with ZGCP (1 mg / mL) in Example 1 for different time periods (0 h, 2 h, 6 h, 12 h and 24 h) detected by the DTNB method;
[0029] Fig.12 The SEM images of ZGCP in Example 1 at different magnifications after reacting with GSH (5 mM) for different times (0 h, 2 h, 6 h, 12 h and 24 h);
[0030] Fig.13 The Cu ion release of ZGCP in Example 1 after reacting with different concentrations of GSH for different time periods;
[0031] Fig.14 is the H2O2 standard curve;
[0032] Fig.15 The UV-Vis curves of the solution of ZGCP (1 mg / mL) and glucose (1 mg / mL) at different time points (1 h, 2 h, 6 h, 12 h and 24 h) in Example 1;
[0033] Fig.16 (a) UV-Vis curves and (b) H2O2 content of the solution of ZGCP (1 mg / mL) and glucose (1 mg / mL) at different time points (1h, 2h, 6h, 12h and 24h) after GSH (5mM) treatment for 12h;
[0034] Fig.17 The UV-Vis curve of the solution after ZGCP (1 mg / mL) and glucose (1 mg / mL) were reacted for 12 hours after being treated with PBS at pH = 5.8 for 12 hours;
[0035] Fig.18 TEM images of ZGCLL at different magnifications;
[0036] Fig.19 Energy dispersive X-ray spectra (Cu, P, Zn and O) of ZGCLL (scale bar: 200 nm);
[0037] Fig. 20 is the XRD pattern of ZGCLL;
[0038] Fig.21 (a) XPS full spectrum, (b) Zn 2p XPS spectrum and (c) Cu 2p XPS spectrum of ZGCLL;
[0039] Fig. 22 The standard curve for detecting GOx by Bradford method;
[0040] Fig.23 (a) UV-Vis curves and (b) GSH quantitative results of the solution after the reaction of GSH (5 mM) and ZGCLL (1 mg / mL) for different time periods (0 h, 2 h, 6 h, 12 h, and 24 h) detected by the DTNB method;
[0041] Fig.24(a) UV-Vis curves and (b) H2O2 content of the ZGCLL (1 mg / mL) and glucose (1 mg / mL) solutions at different time points (1 h, 2 h, 6 h, 12 h and 24 h) after GSH (5 mM) treatment for 12 h;
[0042] Fig.25 is the standard curve for NO detection;
[0043] Fig.26 is the NO production of L-arginine (1 mg / mL) at different pH values at different time points;
[0044] Fig. 27 NO production at different time points in a mixed solution of L-arginine (1 mg / mL) and H2O2 (1 mM) under different treatments (1.0 MHz, 1.0 W / cm2, 5 min);
[0045] Fig.28 The mixed solution of ZGCP (1 mg / mL) and glucose (1 mg / mL) treated with L-arginine (1 mg / mL) and GSH (5 mM, 12 h) was treated with different treatments (1.0 MHz, 1.0 W / cm 2 , 5min) at different time points;
[0046] Fig.29 The mixed solution of ZGCLL (1 mg / mL) and glucose (1 mg / mL) treated with GSH (5 mM, 12 h) was subjected to ultrasound treatment (1.0 MHz, 1.0 W / cm 2 , 5min) at different time points;
[0047] Fig.30 Cell viability of HUVEC and 4T1 cells after co-culture with different concentrations (0-30 ppm) of (a) ZGCP and (b) ZGCLL;
[0048] Fig.31 is the cell survival rate of 4T1 cells after co-culture with different concentrations of L-arginine (0-500 ppm);
[0049] Fig.32 Cell survival rate of 4T1 cells after co-culture with different concentrations of ZGCLL with or without ultrasonic treatment (***p<0.001, **p<0.01 and *p<0.05, n=3, mean±SD);
[0050] Fig.33Fluorescence images of 4T1 cells treated differently after co-staining with Calcein-AM and PI (scale bar: 100 μm); Fluorescence images of 4T1 cells treated differently after co-staining with EdU and Hoechst (scale bar: 50 μm);
[0051] Fig.34 Cell viability of HUVEC and 4T1 cells after co-culture with different concentrations of ZIF-8@Cu-PDA (ZGCP, 0-500 ppm). DETAILED DESCRIPTION
[0052] The Cu-PDA shell of the present invention can respond to the cleavage of GSH in the tumor site to avoid premature degradation and "off-target" of GOx, specifically act on tumor cells, expose internal ZIF-8 to mediate Zn overload and activate GOx to catalyze the reaction of intracellular glucose and oxygen to generate H2O2, and the consumption of glucose can achieve starvation therapy, and work together with Zn ion therapy to aggravate cell oxidative stress. H2O2 can also produce more active ROS under ultrasonic catalysis, and quickly react with the delivered LA to produce high-concentration NO to achieve ultrasonic catalytic gas therapy.
[0053] The exemplary embodiments will be described in detail below, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following exemplary embodiments do not represent all implementations consistent with the present application. Instead, they are only examples of devices and methods consistent with some aspects of the present application as detailed in the attached claims.
[0054] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0055] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0056] The ammonia water in the present invention is a commercially available product, and the ammonia content is 25% to 27%;
[0057] It should be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only an example within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0058] Embodiment 1:
[0059] A method for preparing ZIF-8-GOx@Cu-PDA@liposome-LA nanoparticles may include the following steps:
[0060] Step (1), add 10 mL of 0.194 g / mL 2-methylimidazole aqueous solution to 4 mL of 10 mg / mL GOx solution and stir at room temperature for 20 min, then add 4 mL of 25 mg / mL Zn(NO3)2·6H2O aqueous solution to the above solution. After stirring at room temperature for 30 min, add 20 mg F127 to the reaction system and continue the reaction for 2 h. Wash the reaction product with water by centrifugation for 3-4 times to obtain ZIF-8-GOx nanoparticles, and redisperse in 10 mL of deionized water;
[0061] Step (2), dissolving 12.5 mg of dopamine hydrochloride and 2.8 mg of CuCl2·2H2O in 10 mL of deionized water. Mixing 100 μL of ammonia water and 1 mL of a 10 mg / mL ZIF-8-GOx solution, adding the mixture to the solution and stirring at room temperature in the dark for 5 h. After the reaction is completed, washing the product by centrifugation with water three to four times to obtain ZGCP, and redispersing the mixture in 4 mL of deionized water to obtain a ZGCP solution;
[0062] TEM images of the materials obtained in step 1 and step 2 are shown in Figure 2 and Figure 3 From the figure, it can be seen that the synthesized nanomaterials are spherical particles. The XRD spectra of ZIF-8-GOx obtained in step 1 and ZGCP obtained in step 2 are shown in Figure 5 ; The energy dispersive X-ray spectrum obtained by step 2 of this embodiment ( Figure 4 ) and its XPS spectrum ( Figure 6 ) It can be seen that the synthesized material contains copper and zinc, and the copper ions and zinc ions are successfully and evenly distributed in the nanomaterial, proving the successful synthesis of ZGCP.
[0063] The ZGCP obtained in step 2 was added to GSH to test its GSH consumption capacity. DTNB (4 mg) was dissolved in a buffer solution (1 mL, pH = 8.0) to prepare a DTNB solution. ZGCP or ZGCLL solution (1 mg / mL, 1 mL) was mixed with GSH (5 mM), and the supernatant (20 μL) was collected by centrifugation after different reaction times (0 h, 2 h, 6 h, 12 h and 24 h) and mixed with DTNB solution (50 μL) and buffer (2.5 mL, pH = 7.0). After 15 min of reaction, the absorbance at 350 nm-600 nm was recorded using a UV-visible spectrophotometer, and the absorbance at 412 nm was taken to quantify GSH. Fig.10 is the GSH content in the solution after ZGCP (1 mg / mL) reacted with different concentrations of GSH for 1 h in this example; Fig.11 (a) UV-Vis curve and (b) GSH quantitative result of the solution after ZGCP (1 mg / mL) and GSH (5 mM) were reacted for different time periods (0 h, 2 h, 6 h, 12 h and 24 h). It can be seen that there is a significant consumption of GSH when ZGCP and GSH exist at the same time.
[0064] Then, the ZGCP and GSH obtained in step 2 were mixed and reacted, and SEM images were taken at different times, such as Fig.12 , it can be seen that after reacting with GSH, the shell of ZGCP collapsed and decomposed rapidly, and the particle degradation was obvious, which provided a basis for the exposure of ZIF-8 and GOx and the activation of GOx activity.
[0065] The release of Cu ions in ZGCP after reacting with different concentrations of GSH for different times was analyzed by ICP-OES. Fig.13 As shown in the figure, in the first 4 hours, the Cu ions in ZGCP can be rapidly released in response to GSH, and about 16% of the copper ions are released at 4 h, while in the absence of GSH (i.e., 0 mM GSH), almost no copper ions are released.
[0066] The activity of ZGCP in GOx in response to GSH and its ability to induce H2O2 production were studied by 3,3,5,5-tetramethylbenzidine (TMB) color reaction. ZGCP solution (1 mg / mL, 1 mL) was reacted with GSH (5 mM) for 12 h, and the precipitate was collected by centrifugation and redispersed in 2 mL of glucose solution (1 mg / mL). The supernatant was centrifuged at different reaction time points (1 h, 2 h, 6 h, 12 h and 24 h) to detect the production of H2O2. The test solution (200 μL) was mixed with HRP (1 U / mL, 300 μL) and PBS buffer (1.5 mL, pH = 5.8) for 10 min, and then TMB ethanol solution (2 mM, 300 μL) was added to the system. The absorbance of the solution from 300 nm to 800 nm was recorded using a UV-visible spectrophotometer, and the H2O2 was quantitatively calculated based on the absorbance at 653 nm. In the presence of H2O2, peroxidase catalyzes the redox reaction between H2O2 and TMB, oxidizing TMB to blue ox-TMB. The concentration of H2O2 can be quantitatively analyzed by detecting the characteristic absorption peak intensity of TMB at 653nm. Fig.15 As shown in the figure, when ZGCP directly reacted with glucose at different time points, TMB did not show obvious characteristic peaks, which indicated that no obvious H2O2 was produced and ZGCP itself did not show GOx activity. However, after reacting with GSH (5mM) for 12h, glucose solution was added to the solution. As the reaction time increased, the absorbance of the characteristic peaks of TMB (at 370nm and 653nm) gradually increased, which indicated that the time-dependent H2O2 production ( Fig.16 ).
[0067] Step (3), 6 g DPPC, 4 g cholesterol and 0.5 g DSPE-mPEG were mixed uniformly, the uniform solution was added to chloroform and ultrasonically treated for 10 min using an ultrasonic cleaner, and then evaporated to dryness using a rotary evaporator;
[0068] Step (4), dissolving the liposome sample in 4 mL of water to prepare a liposome solution, mixing 80 μL of the 0.45 mg / μL liposome solution, 1 g of L-arginine and 1 ml of a 10 mg / mL ZGCP solution and treating under ultrasound for 10 min;
[0069] Step (5), washing the mixed solution with water by centrifugation three to four times to obtain the target product ZGCLL nanoparticles.
[0070] Fig.18 TEM images of ZGCLL at different magnifications of this embodiment are shown; it can be seen that the ZGCLL has a three-layer structure, is spherical, and has a particle size of 100-300 nm.
[0071] Fig. 20 is the XRD pattern of ZGCLL in this embodiment; Fig.21 : is the XPS spectrum of ZGCLL of this example; it can be seen that the crystal structure of ZGCLL and the successful coating of Zn and Cu ions are obtained.
[0072] Fig.19 : is the energy dispersive X-ray spectrum (Cu, P, Zn and O) of ZGCLL of this example (scale: 200 nm); it can be seen that Zn and Cu ions are uniformly distributed.
[0073] The ZGCLL obtained in step 5 was added to GSH. The (a) UV-Vis curve and (b) GSH quantitative results of the solution after the reaction of GSH (5 mM) and ZGCLL (1 mg / mL) of this example for different time periods (0 h, 2 h, 6 h, 12 h and 24 h) were detected by DTNB method. It can be seen that when this example exists, the GSH content in the solution is significantly reduced, and ZGCLL has a certain GSH consumption capacity.
[0074] The activity of ZGCLL in GOx in response to GSH and its ability to induce H2O2 production were studied by 3,3,5,5-tetramethylbenzidine (TMB) color reaction. ZGCLL solution (1 mg / mL, 1 mL) was reacted with GSH (5 mM) for 12 h, and the precipitate was collected by centrifugation and redispersed in 2 mL of glucose solution (1 mg / mL). The supernatant was centrifuged at different reaction time points (1 h, 2 h, 6 h, 12 h and 24 h) to detect the production of H2O2. The test solution (200 μL) was mixed with HRP (1 U / mL, 300 μL) and PBS buffer (1.5 mL, pH = 5.8) for 10 min, and then TMB ethanol solution (2 mM, 300 μL) was added to the system. The absorbance of the solution from 300 nm to 800 nm was recorded using a UV-visible spectrophotometer, and the H2O2 was quantitatively calculated based on the absorbance at 653 nm. In the presence of H2O2, peroxidase catalyzes the redox reaction between H2O2 and TMB, oxidizing TMB to blue ox-TMB. The concentration of H2O2 can be quantitatively analyzed by detecting the characteristic absorption peak intensity of TMB at 653nm. Fig.24 As shown in the figure, the (a) UV-Vis curve and (b) H2O2 content of the solution of ZGCLL in this example at different time points (1h, 2h, 6h, 12h and 24h) after being treated with GSH (5mM) for 12h. It can be seen that the example itself does not show GOx activity, but after being treated with GSH, the H2O2 concentration in the solution is significantly increased.
[0075] L-arginine, as an intracellular nitric oxide (NO) gas donor, can be catalytically oxidized to NO and L-citrulline under the action of nitric oxide synthase (NOS), and can also generate NO in response to reactive oxygen species such as H2O2. Ultrasound can convert ultrasonic mechanical energy into chemical energy, catalyze H2O2 to produce reactive oxygen species (O·) with higher oxidative activity, thereby more efficiently oxidizing L-arginine molecules to produce more NO. The nitric oxide generation of ZGCLL under ultrasound was detected using a nitric oxide kit. Specifically, ZGCLL solution (1 mg / mL, 1 mL) was reacted with GSH (5 mM) for 24 h and then centrifuged to collect the precipitate. The precipitate was added to glucose solutions (1 mg / mL, 2 mL) with different pH values and subjected to ultrasonic irradiation (1.0 MHz, 1.0 W / cm 2 , 5min) and NO quantitative detection. 50μL of the test solution, room temperature Griess Reagent I and room temperature Griess Reagent II were added to each well of the 96-well plate in sequence, and the absorbance was measured at 560nm using an ELISA reader, and the NO generation in the system was calculated using the standard curve. Fig.29 As shown, GSH-treated ZGCLL can expose the core GOx and react with the added glucose to generate H2O2, which further reacts with L-arginine under ultrasound catalysis to achieve the massive generation of NO.
[0076] In vitro cell experiments were performed on ZGCLL, using HUVEC human umbilical vein endothelial cells and mouse breast cancer cells 4T1 to evaluate the in vitro cell biocompatibility and therapeutic effects of ZGCP and ZGCLL.
[0077] Calcein-AM and PI co-staining were used to mark the living and dead cells after different treatments, and the effects of ZGCP and ZGCLL on the survival rate of 4T1 cells were further evaluated.
[0078] The effects of ZGCP and ZGCLL on the proliferation ability of 4T1 cells were studied by EdU and Hoechst co-staining.
[0079] like Fig.30 As shown in the figure, the cell survival rates of HUVEC and 4T1 cells after co-culture with ZGCP and ZGCLL at different concentrations (0-30ppm), it can be seen that the survival rate of HUVEC cells cultured with ZGCLL nanoparticles of the present invention is improved compared with ZGCP without liposome-LA layer coating, while the survival rate of 4T1 cells is less improved, indicating that ZGCLL can reduce the damage to normal cells while maintaining the killing power to tumor cells.
[0080] Fig.33 The fluorescence images of 4T1 cells treated differently after co-staining with Calcein-AM and PI (scale: 100 μm) and the fluorescence images of 4T1 cells treated differently after co-staining with EdU and Hoechst (scale: 50 μm) show that compared with the control group and the ultrasound group alone, the ZGCP group, ZGCLL group and ZGCLL+US group all showed significantly weakened green fluorescence, and the proportion of EdU-labeled cells was significantly reduced, indicating that ZGCP, ZGCLL and ZGCLL+US can significantly inhibit the proliferation activity of 4T1 cells. In this embodiment, ZGCLL has the strongest ability to inhibit cell proliferation and induce cell apoptosis when ultrasound is applied.
[0081] The cytotoxicity of ZGCLL at a given concentration to 4T1 cells under ultrasonic treatment was then studied: Fig.32 As shown, compared with the group without ultrasound treatment, the application of ultrasound can promote the cell killing effect of ZGCLL on 4T1 to a certain extent, which is related to the reaction of ZGCLL catalyzing Zn overload and GOx-induced H2O2 with L-arginine to produce NO under ultrasound, thereby inducing NO gas therapy.
[0082] Embodiment 2:
[0083] A method for preparing ZIF-8-GOx@Cu-PDA@liposome-LA nanoparticles may include the following steps:
[0084] Step (1), add 12 mL of 0.194 g / ml 2-methylimidazole aqueous solution to 5 mL of 10 mg / mL GOx solution and stir at room temperature for 20 min, then add 4 mL of 25 mg / mL Zn(NO3)2·6H2O aqueous solution to the above solution. After stirring at room temperature for 30 min, add 20 mg F127 to the reaction system and continue the reaction for 2 h. Wash the reaction product with water by centrifugation 3-4 times to obtain ZIF-8-GOx nanoparticles, and redisperse in 10 mL of deionized water;
[0085] Step (2), 8.75 mg of dopamine hydrochloride and 2 mg of CuCl2·2H2O were dissolved in 16 mL of deionized water. 200 μL of ammonia water and 2 mL of a 10 mg / mL ZIF-8-GOx solution were mixed and added to the above solution and stirred at room temperature in the dark for 5 h. After the reaction was completed, the product was washed with water by centrifugation for 3-4 times to obtain ZGCP, and redispersed in 4 mL of deionized water to obtain a ZGCP solution;
[0086] Step (3), 12 g DPPC, 8 g cholesterol and 1 g DSPE-mPEG were mixed uniformly, the uniform solution was added to chloroform and ultrasonically treated for 10 min using an ultrasonic cleaner, and then evaporated to dryness using a rotary evaporator;
[0087] Step (4), dissolving the liposome sample in 4 mL of water to prepare a liposome solution with a concentration of 0.45 mg / μL, mixing 100 μL of the liposome solution, 1.25 g of L-arginine and 1.25 mL of a ZGCP solution with a concentration of 10 mg / mL and treating under ultrasound for 10 min;
[0088] Step (5), washing the mixed solution with water by centrifugation for 3-4 times to obtain the target product ZGCLL nanoparticles.
[0089] The samples of this example were studied using the characterization method of Example 1. It was found that the characterization results of the products obtained in this example were similar to those of Example 1, both of which were spherical nanoparticles with a three-layer structure of 100-300 nm.
[0090] Embodiment 3:
[0091] A method for preparing ZIF-8-GOx@Cu-PDA@lipsome-LA nanoparticles may include the following steps:
[0092] Step (1), add 100 mL of 0.194 g / mL 2-methylimidazole aqueous solution to 40 mL of 10 mg / mL GOx solution and stir at room temperature for 20 min, then add 40 mL of 25 mg / mL Zn(NO3)2·6H2O aqueous solution to the above solution. After stirring at room temperature for 30 min, add 200 mg F127 to the reaction system and continue the reaction for 2 h. Wash the reaction product with water by centrifugation for 3-4 times to obtain ZIF-8-GOx nanoparticles, and redisperse in 100 mL of deionized water;
[0093] Step (2), 87.5 mg dopamine hydrochloride and 20 mg CuCl2·2H2O were dissolved in 160 mL deionized water. 2 mL ammonia water was mixed with 20 mL ZIF-8-GOx solution with a concentration of 10 mg / mL, and then added to the above solution and stirred at room temperature in the dark for 5 h. After the reaction was completed, the product was centrifuged and washed with water for 3-4 times to obtain ZGCP, and then redispersed in 40 mL deionized water to obtain a ZGCP solution;
[0094] Step (3), 120 g DPPC, 80 g cholesterol and 10 g DSPE-mPEG were mixed uniformly, the uniform solution was added to chloroform and ultrasonically treated for 15 min using an ultrasonic cleaner, and then evaporated to dryness using a rotary evaporator;
[0095] Step (4), dissolving the liposome sample in 40 mL of water to prepare a liposome solution with a concentration of 0.45 mg / μL, mixing 1000 μL of the liposome solution, 12.5 g of L-arginine and 12.5 ml of a 10 mg / mL ZGCP solution and treating under ultrasound for 15 min;
[0096] Step (5), washing the mixed solution with water by centrifugation for 3-4 times to obtain the target product ZGCLL nanoparticles.
[0097] The samples of this example were studied using the characterization method of Example 1. It was found that the characterization results of the products obtained in this example were similar to those of Example 1, both of which were spherical nanoparticles with a three-layer structure of 100-300 nm.
Claims
1. A nanoparticle for tumor targeted therapy, characterized in that: It has a core-shell structure, and includes, from the inside to the outside, a ZIF-8-GOx core, a Cu-PDA layer, and a liposome-LA layer, wherein the ZIF-8-GOx core is ZIF-8 encapsulating glucose oxidase; in the Cu-PDA layer, copper ions are uniformly distributed in polydopamine; in the liposome-LA layer, L-arginine is dispersed in liposomes.
2. The nanoparticles for tumor targeted therapy according to claim 1, characterized in that: The nanoparticles are spherical and have a particle size of 100-300nm.
3. The method for preparing nanoparticles according to claim 1, characterized in that: include: A Cu-PDA layer was coated on the outside of ZIF-8-GOx to form ZGCP; And, a liposome layer is coated on the outside of ZGCP to obtain ZGCLL nanoparticles.
4. The preparation method according to claim 3, characterized in that: ZIF-8-GOx was prepared by the following method: 10-12 mL of 0.194 g / mL 2-methylimidazole aqueous solution was added to 4-5 mL of 10 mg / mL GOx solution and stirred at room temperature for 20 min. Subsequently, 4 mL of 25 mg / mL Zn(NO3)2·6H2O aqueous solution was added to the above solution. After stirring at room temperature for 30 min, 20 mg of polyether F127 was added to the reaction system and the reaction was continued for 2 h. The reaction product was centrifuged and washed with water for 3-4 times to obtain ZIF-8-GOx nanoparticles.
5. The preparation method according to claim 3, characterized in that: The method of coating the ZIF-8-GOx with a Cu-PDA layer specifically includes: adding 1-2 mL of a 10 mg / mL ZIF-8-GOx nanoparticle dispersion and 100-200 μL of ammonia water to a 10-16 mL mixed aqueous solution containing 8.75-12.5 mg of dopamine hydrochloride and 2-2.8 g of CuCl2·2H2O, and reacting for 5 hours in the dark; after the reaction, the product is centrifuged and washed with water for 3-4 times to obtain ZGCP.
6. The preparation method according to claim 3, characterized in that: The liposomes coated on the outside of ZGCP specifically include: 1-1.25 mL of 10 mg / mL ZGCP dispersion was mixed with 80-100 μL of 0.45 mg / μL liposome solution and 1-1.25 g L-arginine, and then subjected to ultrasonic treatment; the target product ZGCLL was obtained by centrifugation and washing with water for 3-4 times.
7. The preparation method according to claim 6, characterized in that: The liposome solution was prepared by the following method: DPPC, cholesterol, and DSPE-mPEG were mixed in a mass ratio of 6:4:0.5 to form a homogeneous solution; the homogeneous solution was added to chloroform and subjected to ultrasonic treatment, and then evaporated to dryness using a rotary evaporator.
8. The preparation method according to claim 7, characterized in that: The ultrasonic treatment time is 10 minutes.
9. Use of the nanoparticles according to claim 1 as a drug for ultrasound-assisted tumor treatment.
10. A tumor treatment system, characterized in that: include: A drug delivery system for inputting the requirement of claim 1; Ultrasonic system, used for inputting ultrasonic waves.
Citation Information
Patent Citations
Application of cancer cell membrane bionic nano-reactor AGZ@CM in preparation of anti-cancer drugs
CN111494339A
Nano composite material capable of generating hydrogen peroxide through in-situ autocatalysis and continuously releasing NO and free radicals as well as preparation method and application of nano composite material
CN114106354A
Nanometer prodrug for promoting release of nitric oxide gas through ultrasonic piezoelectric catalytic effect as well as preparation method and application of nanometer prodrug
CN116236587A
Self-cascade enhanced multi-mode tumor treatment nano-drug as well as preparation method and application thereof
CN117427161A
Double-layer microneedle for diabetes wound healing as well as preparation method and application of double-layer microneedle
CN118021706A
